Overcoming disadvantage. - Council for Aboriginal Reconciliation (Australia) (Kingston, A.C.T. : Council for Aboriginal Reconciliation, 2000)
Provides detail on ways to implement the national Strategy to Overcome Disadvantage, one of the four strategies in the Roadmap for Reconciliation; understanding disadvantage in education; health and well-being; employment; housing and accommodation; law and justice; communities; outlines actions we can take: leadership at all levels; buidling stronger communities and equal partnerships; better service delivery; accountability and benchmarking; appropriate funding arrangements; gives examples of what the strategy could mean in practice; presents statistics of social and economic well-being.
"Ways to implement the national strategy to overcome disadvantage, one of four national strategies in the Roadmap for reconciliation" -- Cover.
Cover title.
Keywords: Aboriginal Australians -- Economic conditions; Torres Strait Islanders -- Social conditions; Aboriginal Australians -- Social conditions; Race relations - Reconciliation; Socioeconomic conditions; Law - Legal system; Housing; Health; Education; Employment; Social welfare - Government; Australia -- Race relations; Torres Strait Islanders -- Economic conditions; Australia